DIABETIC FOOT INFECTION PROFILE, COMMON PATHOGEN AND ANTIBIOTIC SENSITIVITY - Soelistijo, Soebagijo Adi; Ardiany, Deasy (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Foot infections are the major complications of diabetes mellitus and lead to the development of amputation. The aim of this study was to establish the biochemical and bacteriological profile of Diabetic foot ulcer (DFU). METHODOLOGY This was a cross-sectional observational study performed at Surabaya tertiary hospital. The DFU patients got measured their ABI, hematological, biochemical examination. The grading of DFU was carried out as per Wagner’s system. RESULTS A total of 30 patients with DFU were included. 56.7% were males and 43.3% were females with average age of 54.7 years old. The mean WBC was 19,236±6,866.4/ mm3, mean HbA1c was 9.88±1.9% and mean eGFR was 62.37±32.4 mL/min/1.73 m2. The 3rd grade ulcers and Proteus Mirabilis were the most predominant ulcers and pathogens respectively (36.7% and 30%). The culture results were 100% sensitive to amikacin, piperacillin-tazobactam, cefoperazone-sulbactam, and imipenem. CONCLUSION In this study, Wagner’s grade 3 and Proteus Mirabilis were the most predominant ulcers and pathogens, respectively. Amikacin, piperacillin-tazobactam, cefoperazone-sulbactam, and imipenem were the most sensitive antibiotics.